Employees Perception on Gender diversity on banking performance in Kathmandu valley - Niranjan Devkota; Sushma Adhikari; Seeprata Parajuli; Udbodh Bhandari; Udaya Raj Poudel (Qubahan Academic Journal)
Studying gender diversity in firm performance has been the subject of research request for more than three decades now. Yet, in context of Nepal, study related to the issue is still not abundant. Therefore, this study aims to study the present status of gender diversity on banking performance in Nepalese context that includes several benefits, challenges associated with it and policies and measures that need to be taken to promote gender diversity. The study adopted descriptive cross section research design with the survey questionnaire technique. With the help of convenient sampling technique 300 bank employees were selected purposively from all 27 A grade commercial banks residing Kathmandu valley. The study results that 100% respondents working in commercial banks in Kathmandu valley were aware about gender diversity and most of them have been aware gender diversity through their family and social media. Interestingly, this study also found that employees are not facing any challenges regarding gender diversity signifying that Nepalese commercial Banks have been practicing gender diversity friendly working environment. Similarly, building an inclusive workplace could be one of the best managerial solutions for maintaining and enhancing gender diversity.